Centrifugal and Centripetal Forces in Radical New Product Development Under Time Pressure - Sheremata, Willow A. (Academy of Management Review, 2000)
Organizations must be ambidextrous to successfully develop new products—they must act creatively as well as collectively. However, how to do this is not clear. The author analyzes this problem and reviews the literature in terms of two opposing forces: the first increases the quantity and quality of ideas, information, and knowledge available for creative action while the second integrates these things into collective action. The author then models these forces to explain how the coexistence of contradictory structural elements and processes increases the probability of successful development.